THE EFFECT OF SERVICE QUALITY TOWARDS CUSTOMER SATISFACTION AND REVISIT INTENTION AT WARUNK UPNORMAL PAHLAWAN TRIP IN KOTA MALANG (A Study on Students of Universitas Brawijaya) - I Made Pradna Wirakananda (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This research aimed to determine the effect of service quality towards customer satisfaction and revisit intention variables. This is an explanatory research that explained the relationship and influence between one variable and another by submitting a hypothesis. This research used a sample of 200 respondents by online questionnaires distribution. The sample consisted of respondents who had visited Warunk Upnormal Pahlawan Trip in kota Malang. Data were analysed with path analysis using the SPSS 21 program. The test results of the four hypotheses concluded that service quality has a significant effect on customer satisfaction and revisit intention. Customer satisfaction has a significant effect on revisit intention. In addition, customer satisfaction can significantly mediate service quality towards revisit intention. Hopefully, this research can become a reference for Warunk Upnormal Pahlawan Trip to improve and enhance their business performance in the future. Keywords: Service Quality, Customer Satisfaction, Revisit Intention